EKSISTENSI INDUSTRI HALAL FOOD DI JEPANG - Budi Mulyadi (KIRYOKU, 2023)
Japan is a favorite destination for foreign tourists, especially Indonesia and other Middle Eastern countries. This has made Japan very aggressive in developing the halal food industry among Muslim tourists. Japan is a country where the majority of the population is Buddhist and Shinto. Knowledge of Islam and things related to halal is still limited. Therefore, this research conducted to get to know whether the halal industry especially halal food restaurant in Japan, is already well available and how the certification halal is in Japan. This research focuses on the origin of the halal industry in Japan, the need for halal food in Japan, the halal food restaurant in Japan, and the certification halal in Japan. The research data is taken from journals and websites that are relevant to the research theme. The data's results show that the number of Muslim population has increased from year to year and this also certainly makes the demand for halal food increasing. It is make an competition between the halal food industry in Japan. Therefore, nowadays there are many halal food restaurants in Japan and they are competing to get halal certification in Japan.